SLOWING THE GROWTH OF AN AGGRESSIVE GLIOBLASTOMA CELL LINE BY ENHANCER RNA SILENCING DEPENDS ON THE KNOCKDOWN METHOD - Ekaterina Statsevich; Anastasiia Simonova; Anastasiya Poteryakhina; Uliana Beri; Elvina Bogomolova; Aksinya Uvarova; Matvey Murashko; Elina Zheremyan; Kirill Korneev; Dmitry Kuprash; Denis Demin (Медицинская иммунология, 2019)
AbstractGlioblastoma is the most frequent and aggressive brain tumor, with a low survival rate. One of the challenges in treating glioblastoma is the resistance of cells to temozolomide, the main chemical agent used to fight the disease. The STAT3 gene is known to play a significant role in the growth and metastasis of tumor cells. Inhibition of STAT3 or suppression of its expression reduces the resistance of glioblastoma cells to temozolomide. Enhancer RNAs (eRNAs) are non-coding RNAs that are transcribed from enhancer regions. eRNAs can affect the expression of key genes of various biological processes, including oncogenes. Previously, we conducted a search for an eRNAs that may potentially affect glioblastoma cell resistance to temozolomide. Knockdown of TMZR1-eRNA (ENSG00000289579) in DBTRG-05MG cell line resulted in decreased STAT3 gene expression and increased cell sensitivity to temozolomide. The effect of enhancer RNA knockdown on STAT3 gene promoter activity has been shown both alone and together with the enhancer from which this eRNA is transcribed. The current study was designed to investigate the potency of TMZR1-eRNA in a glioblastoma cell line U-251. Compared to the previously studied cell line DBTRG-05MG, the U-251 cell line is more aggressive, has a higher proliferation rate and was derived from patient tissue at a later stage of the disease. Knockdown of TMZR1-eRNA by small interfering RNAs resulted in a decrease in STAT3 gene expression. No effect on cell growth was observed both when temozolomide was added and in control conditions of culture medium with DMSO. To study the effect of constitutive suppression of eRNAs, U-251 cell cultures expressing short hairpin RNA (shRNA) targeting TMZR1-eRNA and control vector were transduced. A significant increase in STAT3 mRNA expression was observed in the obtained cell lines relative to the control. At the same time, viability analysis demonstrated a significant slowdown in the growth rate of the cell line expressing short hairpin RNAs to TMZR1-eRNA compared to the control. A significant effect was observed both when temozolomide was added and in culture medium with DMSO.